2021
DOI: 10.1007/s12070-021-02799-z
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Treatment Outcomes of Music Therapy, Tinnitus Maskers and Pharmacotherpy in Chronic Subjective Tinnitus

Abstract: Tinnitus represents one of the most common and distressing otologic problems, and it causes various somatic and psychological disorders that interfere with the quality of life. This study aimed to compare the outcome of music therapy, tinnitus maskers and pharmacotherapy on patients with chronic tinnitus, to observe and analyse the etiological factors of tinnitus and to find out whether music can be used as an active listening mode by which tinnitus perception can be decreased. This was a comparative longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For THI, the mean difference score between the pre-and post-treatment was available for thirteen trials. [13,15,16,18,[23][24][25][26][27][28][29][30][31] A random-effect model was used to analyze the data (I 2 = 73.8% > 50%, P = .000 < .1). Compared with before treatment, music therapy significantly reduces the THI score (SMD = −0.88, 95%CI −1.15 to −0.6, P = .000 < .001) (Fig.…”
Section: Meta-analysis Of the Effect Of Music Therapy On Severity Of ...mentioning
confidence: 99%
See 2 more Smart Citations
“…For THI, the mean difference score between the pre-and post-treatment was available for thirteen trials. [13,15,16,18,[23][24][25][26][27][28][29][30][31] A random-effect model was used to analyze the data (I 2 = 73.8% > 50%, P = .000 < .1). Compared with before treatment, music therapy significantly reduces the THI score (SMD = −0.88, 95%CI −1.15 to −0.6, P = .000 < .001) (Fig.…”
Section: Meta-analysis Of the Effect Of Music Therapy On Severity Of ...mentioning
confidence: 99%
“…Six trials recorded the mean difference score between the pre-and post-treatment. [13,[26][27][28]30] A fixed-effect model was used to analyze the data (I 2 = 20.4% < 50%, P = .285 > .1). We found that music therapy significantly decreases the visual analog scale-loudness score (SMD = −0.86, 95%CI −1.08 to −0.64, P = .003 < .05) (Fig.…”
Section: Meta-analysis Of the Effect Of Music Therapy On Tinnitus Lou...mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] [21,22] [ [23][24][25][26][27][28] surgical procedures, behavioral audio therapy, tinnitus masking devices, transcranial magnetic stimulation, and psychotherapy were also suggested. [1,3,16,19,29] The aim of this study is to investigate the use of clonazepam as an effective treatment for idiopathic tinnitus or to control the severity of its impact on patients' quality of life.…”
Section: Background and Objectivesmentioning
confidence: 99%